The Impact of Implementing New Public Management, Performance Budget Reporting Models in Educational Institutions - Dwi Susanto, Ari (Riviera Publishing, 2023)
The public administration reforms of the late 1970s brought about revolutionary changes in the delivery of social services and the accounting for government spending and government organizations. A significant challenge Indonesian educational institutions face is allocating resources according to the steps to be taken. Empirical evidence shows that implementing planning and budgeting in school management still needs to be more efficient and full of obstacles. So that the purpose of this study is to find out and analyze the impact of new public management, a model of reporting performance budgets on educational institutions. This research is part of qualitative research using a systematic review approach. Based on the synthesis of the literature review that has been carried out, the impact of implementing the new public management, the performance budgeting reporting paradigm in educational institutions can be summarized as follows: 1) Due to limited available resources, performance-based budgeting is very profitable. 2) A More Comprehensive and Integrated Budget Establishment of an integrated and comprehensive budget is the second shift in the budget system. 3) Preparation of budget and financial reports is the duty and effort of all elements in the school, not only the treasurer. And 4) Structured Governance Pattern. New public management and performance budget reporting models can have a significant impact on educational institutions. By increasing accountability, increasing transparency, increasing efficiency, and improving performance standards.